(untitled) (Journal of the College of Basic Education, 2022)
The designs of clothing costumes and their employment in sculptural monuments in Europe and their utilitarian value as well as their expressive and functional value, and because they are affected like other arts as the applied art that takes from nature its aesthetic, and that these designs implemented in the world express belonging and originality and mimic symbols and elements And vocabulary that expresses intellectual, cultural and artistic contents. And since this trend was not studied in a formula that evokes its functional, expressive and aesthetic dimensions, as well as employing design concepts to achieve those dimensions. The researcher directed to study this through four chapters, in the first of which he sought to clarify the research problem, its importance, limits, objectives and terminology. As for the second chapter, it included the theoretical framework, in which the researcher tackled the study of the diversity of fashion designs in the Renaissance as a first topic, followed by the study of contemporary fashion designs on the formations of sculptural monuments as a second topic. Through this, the researcher reached to put the most important indicators as a scientific material that benefited from them in its procedures and research method in analyzing the content of the samples. The analysis, which was represented in the design of an analysis unit (the integrated communication unit) as it carries an integrated communication idea from which ideas can be derived through analysis, and thus formed by the researcher (One sample and four models have). The research also included a chapter on findings, recommendations and suggestions